2014
DOI: 10.1007/978-3-319-08509-8_8
|View full text |Cite
|
Sign up to set email alerts
|

PExy: The Other Side of Exploit Kits

Abstract: Abstract. The drive-by download scene has changed dramatically in the last few years. What was a disorganized ad-hoc generation of malicious pages by individuals has evolved into sophisticated, easily extensible frameworks that incorporate multiple exploits at the same time and are highly configurable. We are now dealing with exploit kits. In this paper we focus on the server-side part of drive-by downloads by automatically analyzing the source code of multiple exploit kits. We discover through static analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Most previous academic work [8][9][10][11] focused on the server-side source code of the EK families and conducted static source code analysis mostly on PHP code. While the EK families they analyzed leaked behind the scenes, the current EK families that we analyzed are not leaked online yet.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous academic work [8][9][10][11] focused on the server-side source code of the EK families and conducted static source code analysis mostly on PHP code. While the EK families they analyzed leaked behind the scenes, the current EK families that we analyzed are not leaked online yet.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some EK families prefer to serve more stable exploits, where attackers get a lower but steadier infection pace over time. De Maio et al executed an analysis, PExy, on the source code of over 50 EKs in 37 families [6]. They also worked with EKs in off-line mode in their laboratories and via automated static source code analysis, where they produced all combinations of HTTP request parameters (in particular URL and user-agents) that cause an EK to trigger an infection.…”
Section: Related Workmentioning
confidence: 99%
“…Kotov et al [11] showed typical components of exploit kits based on the source codes analysis of 30 exploit kits. Maio et al [12] also analyzed the source codes of exploit kits and reported behavior of exploit kit at the server side. According to [11] and [12], exploit kits have the following four components:…”
Section: Exploit Kit's Componentsmentioning
confidence: 99%